2003
DOI: 10.1080/09603100210161965
|View full text |Cite
|
Sign up to set email alerts
|

Stock market integration and financial crises: the case of Asia

Abstract: This study examines long-run relationships and short-run dynamic causal linkages among the US, Japanese, and ten Asian emerging stock markets, with the particular attention to the 1997-1998 Asian financial crisis. Extending related empirical studies, comparative analyses of pre-crisis, crisis, and post-crisis periods are conducted to comprehensively evaluate how stock market integration is affected by financial crises. In general, the results for the case of Asia show that both long-run cointegration relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(125 citation statements)
references
References 28 publications
13
107
0
5
Order By: Relevance
“…Previous literatures by applying mostly traditional unit root tests viz., ADF and PP (Yuhn, 1997;Yang et al, 2003;Elyasiani and Zhao, 2008;Fadhlaoui et al (2009) mostly have found nonstationary equity price series for the U.S., Germany and Japan similar to the results achieved in the current research. Also Neaime (2005) and Yu and Hassan (2008) eported the same result for Saudi Arabia and also Neaime (2005) informed non-stationary series for Kuwait similar to other selected countries in the current research.…”
Section: Empirical Results Of Unit Root Test Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Previous literatures by applying mostly traditional unit root tests viz., ADF and PP (Yuhn, 1997;Yang et al, 2003;Elyasiani and Zhao, 2008;Fadhlaoui et al (2009) mostly have found nonstationary equity price series for the U.S., Germany and Japan similar to the results achieved in the current research. Also Neaime (2005) and Yu and Hassan (2008) eported the same result for Saudi Arabia and also Neaime (2005) informed non-stationary series for Kuwait similar to other selected countries in the current research.…”
Section: Empirical Results Of Unit Root Test Analysissupporting
confidence: 88%
“…Most of these analyses have selected some developed and developing countries and dominantly have focused on equity markets. A partial list of such work includes (Fadhlaoui et al, 2009;Yu and Hassan, 2008;Soofi, 2008;Elyasiani and Zhao, 2008;Neaime, 2005;Yang et al, 2003;Bessler and Yang, 2003;Yuhn, 1997). Notably, these studies have applied similar methods for their analysis.…”
Section: Ajasmentioning
confidence: 99%
“…The role of Japan as the leader in the region has been highly controversial in this debate. While Masih and Masih (2001) as well as Ghosh et al (1999) concluded that Japan is a market leader, other researches (Yang et al, 2003) suggest that Japan does not play a pivotal role in non-crisis periods. A few other studies have shown that especially Hong Kong is the most influential stock market in Asia (e.g., Masih and Masih, 1999;Dekker et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These mixed evidences pose an important empirical question; are inter-linkage among stock markets time sensitive? In this context, it is worthwhile to mention few noteworthy studies namely Sheng(2000), Cifarelli (2000), Hashmi (2001), Tan (2001), Ratanapakorna (2002), Jang (2002), Yang(2002), Kim (2005), Fan (2003), Melle (2002), Click and Plummer (2005), Lucey and Voronkova(2008) etc. These studies have concentrated on the stock market integration during 1997-1998 Asian financial crises and found that there is shift in the pattern of return and volatility transmission during crisis period.…”
Section: Introductionmentioning
confidence: 99%